Buddhism and Medicine: An Anthology of Modern and Contemporary Sources - Salguero, C. Pierce (Columbia University Press, 2019)
A companion to Buddhism and Medicine: An Anthology of Premodern Sources, this work presents a collection of modern and contemporary texts and conversations from across the Buddhist world dealing with the multifaceted relationship between Buddhism and medicine covering the early modern period to the present.